Aspects de météopathologie des conjonctivites en phase hiverno-printanière à Sfax (Centre-Est de la Tunisie) - Mounir Jarraya (EchoGéo)
The morbidity related to conjunctivitis is influenced by the climatic conditions in Sfax. In fact, the frequency of consultations for conjunctivitis - recorded by Primary Health Care Centers-, during the winter-spring period, correlates with the evolution of the thermal situation. The analysis of the increase in the morbidity rate during this period enables us to determine specific weather-pathological aspects including the transition from winter freshness to spring coolness as well as the predominance of a given type of conjunctivitis in accordance with the season. The latter represent the major factors.